2015
DOI: 10.1142/s0218127415500716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Discontinuity Induced Bifurcations in a Dual Input DC-DC Converter

Abstract: DC-DC power converters with multiple inputs and a single output are used in numerous applications where multiple sources, e.g. two or more renewable energy sources and/or a battery, feed a single load. In this work, a classical boost converter topology with two input branches connected to two different sources is chosen, with each branch independently being controlled by a separate peak current mode controller. We demonstrate for the first time that even though this converter is similar to other well known top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the contrary, the discrete‐time model can provide abundant information to characterize both high‐ and low‐frequency dynamical behaviors of power switching converters including MPCs in detail 19,21,23,24 . Giaouris et al developed the discrete‐time model of the dual‐input Boost converter and then explained those observed bifurcation phenomena 25 . Benadero et al proposed a piecewise linear continuous map to analyze the nonsmooth bifurcation phenomena in a single‐inductor dual‐output DC‐DC converter 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the discrete‐time model can provide abundant information to characterize both high‐ and low‐frequency dynamical behaviors of power switching converters including MPCs in detail 19,21,23,24 . Giaouris et al developed the discrete‐time model of the dual‐input Boost converter and then explained those observed bifurcation phenomena 25 . Benadero et al proposed a piecewise linear continuous map to analyze the nonsmooth bifurcation phenomena in a single‐inductor dual‐output DC‐DC converter 26 .…”
Section: Introductionmentioning
confidence: 99%
“…19,21,23,24 Giaouris et al developed the discrete-time model of the dual-input Boost converter and then explained those observed bifurcation phenomena. 25 Benadero et al proposed a piecewise linear continuous map to analyze the nonsmooth bifurcation phenomena in a single-inductor dual-output DC-DC converter. 26 Sequentially, Xiong et al identified and analyzed the nonsmooth bifurcation in a double-input Boost/Buck-Boost DC-DC converter by using a discrete-time mapping model.…”
mentioning
confidence: 99%
“…Nonlinear phenomena of DC-DC converters have been studied for many years. Previous literature mainly focus on peak current mode Boost converter [12][13][14] and current-mode Buck-Boost converter, [15][16][17] while research on peak current mode Buck converter started relatively late, and most of them employ an approximate one-dimensional discrete model, which fails to reflect the actual working situations of the converters. [3,18] Although there are some research studies that use a two-dimensional discrete model, their physical meanings are ambiguous.…”
Section: Introductionmentioning
confidence: 99%